TOKSISITAS LIMBAH CAIR KELAPA SAWIT TERHADAP IKAN NILA (Oreochromis niloticus Linneus 1758) DAN IKAN BANDENG (Chanos chanos Froskall 1755) - Ilham Zulfahmi; Muliari Muliari; Ira Mawaddah (Universitas Musamus, Merauke, Papua, 2017)
Toxicity test is useful tools to determine the level of toxicity from a substance or pollutant. It also used for routine monitoring of a waste water. This study was conducted from August to September 2016 in Laboratory of Aquaculture, University of Almuslim. The aims of this study were to (1) determine the LC50 value of palm oil mill effluent on Tilapia and milkfish, (2) To describe the impact of palm oil mill effluent on tilapia and milkfish behavior. Tilapia used has weight range of 9-10 g and a length of 7-9 cm, meanwhile milkfish used has a weight range of 9-10 g and a length of 11-13 cm. Fish mortality was observed at 12, 24, 48, 72 and 96 hours. Concentrations of palm oil mill effluent used to acute toxicityof tilapia was 4,517 mg/L, 6,801 mg/L, 10,239 mg/L and 15,414 mg/L, meanwhile concentrations of palm oil mill effluent used to Acute toxicity of milkfish was 6,915 mg/L, 9,563 mg/L, 13,225 mg/L and 18,289 mg/L, respectively. LC50-96 hours of palm oil mill effluent on Tilapia was 15,65 mg/L, whereas for fish milkfish was 14,16 mg/L. Palm oil mill effluent gave negative influence on behavior for both of test fish. The negative effects shown namely slow activity gestures and movements of gill operculum, movement without direction and an excessive amount of mucus on fish skin surface